Participatory modelling to improve partnership schemes for future Community-Based Forest Management in Sumbawa District, Indonesia - Suwarno, A.; Nawir, A.A.; Julmansyah; Kurniawan (2009)
As part of its Community-Based Forest Management (CBFM) Programme, the local government of Sumbawa District in West Nusa Tenggara Province of Eastern Indonesia initiated a partnership programme between the Forestry District Agency and tree grower cooperatives in 2002. The partnership scheme aims to reduce illegal logging and forest encroachment on abandoned state plantations initially developed in 1986. However, the cooperatives have no secure full rights to harvest the mature teak trees (Tectona grandis) inside the plantations, as important incentives to maintain their commitment. This paper aims to explore the potential benefits of different scenarios, as the basis for convincing the Ministry of Forestry (MoF) to give full secure rights to the local communities. In this study, we used a participatory modelling approach, to identify problems and to define future scenarios of partnership arrangements with the local key stakeholders. This research used the concept of system dynamics modelling, which included the two concepts of systems thinking and resilience. As a management tool, the visualisation of the management alternatives and their associated impacts had stimulated the community’s awareness of the importance of protecting the teak plantations from illegal logging and forest encroachment. The simulation results have also shown how granting local communities a full secure access to manage the state forest does not necessarily reduce the revenue for the government at all levels. 2009 Elsevier Ltd. All rights reserved